Effects of experiential training for the preservation of iconic traits about psychosocial norms: quasi-experimental design - Abregú Tueros, Luis Fidel (2023)
Background: In occupational health management experiential trainings for the prevention of psychosocial risks in the country are very low despite their benefits for both workers and employers. Objective: To compare over time the degree of preservation of cognitive-emotional content with the insertion of dissuasive phrases (group A) versus persuasive phrases (group B), for compliance with psychosocial health regulations in the workplace of a group of professionals from the Peruvian Amazon. Method: Quasi-experimental design of two groups pre- and post-test, the latter stage of three measurements. Thirty-two professionals (n=16 per group), ages 22 to 36 years, participated. Training lasted 18 hours spaced over six weeks (December 2018 and January 2019). Results: In group "A" after reaching 91.4% performance in post-test-1 until 90 days there was a decrease (VP: -8.1%; F2/30 = 14.69; p = .0001); from 30 days to 90 days the decrease tended to stabilise (t = 1.08; p < .345). In group "B" the decrease was greater (VP= -11.1%; F2/30 = 8.29; p= .001). Conclusion: Experiential training with a neurolearning approach can improve the preservation of content with the insertion of dissuasive phrases about psychosocial norms at work over persuasive phrases.